The psychotherapeutic implications of functional neuroimaging studies of anxiety disorders. (October 2013) - Cheung, Peter
Objective: To explore and discuss the psychotherapeutic implications of functional neuroimaging findings in anxiety disorders. Conclusions: Therapeutic implications of the neural system dysfunctions found in functional neuroimaging studies of anxiety disorders include: emotional dysregulation can probably be found in all anxiety disorders except obsessive compulsive disorder and needs to be addressed; the probable salience of enhancing implicit emotion regulation in improving overall treatment outcome; the importance of addressing insecure attachment in establishing and maintaining the therapeutic relationship; the need to enhance the reward-approach system especially in chronic treatment-resistant patients; the need to address traumatic memory in anxiety disorders other than PTSD among those with a traumatic history. There is likely to be a need for therapeutic techniques and strategies of different psychotherapy schools to be utilized to adequately address the various neural dysfunctions in patients with anxiety disorders.